Evaluasi kualitas estetika dan daya dukung Taman Bukit Bougenville Kota Singkawang - Chandra, Chandra; Ruliyansyah, Agus; Pramulya, Muhammad (Jurnal Arsitektur Lansekap, 2018)
Evaluation of Aesthetical Quality and Carrying Capacity Bougenville Hill Park City of Singkawang. Bougenville Hill Park is part of the Green Open Space of the city that has ecological, social, economic and aesthetic functions. Aesthetic function is related to the value of beauty and becomes the main attraction for visitors. The purpose of this research is to determine and assess the quality of the park, determine the level of beauty based on respondents' perceptions, park carrying capacity analysis and evaluate the quality of the landscape based on the estimates of the beauty and carrying capacity of Bougenville Hill Park. This research used Scenic Beauty Estimation (SBE) method for evaluation of landscape aesthetic quality and Cifuentes (1992) method with physical carrying capacity for calculation of carrying capacity. The results show the landscape with the lowest SBE value based on the assessment of student and visitor respondents are in landscape 1. Landscapes with the highest SBE score based on students' SBE ratings are in landscape 12. While based on the assessment of visitor SBE, landscape with the highest SBE value is found in landscape 20. Based on the calculation of carrying capacity, the threshold of visitors of Bougenville Hill Park that can be done in 1 day is 72 people who move within the 6 ha area. Some management recommendations are proposed to maintain and improve the aesthetic quality and carrying capacity of Bougenville Hill Park such as maintenance and conservation measures.